Can Capitalists Afford a Trumped Recovery? - Shimshon Bichler; Jonathan Nitzan (The Bichler and Nitzan Archives, 2017)
The presidential election of Donald Trump has rekindled hopes for a U.S. recovery. The new president promises to `make America great again', partly by creating many millions of new jobs for U.S. workers, and judging by the rising stock market, capitalists seem to love his narrative. But if Trump actually delivers on his promise, their attitude is likely to change radically. In our 2016 paper, `A CasP Model of the Stock Market', we developed the concept of a `CasP policy cycle', the idea that government policy, insofar as it caters to the imperative of capitalized power, favours low employment growth in order to enable low rates of interest and sustain the capitalist share of income. Should Trump proceeds with and succeeds in reversing this CasP policy cycle, his authoritarianism may end up undermining rather than boosting capitalized power. In this sense, his regime could well mark the beginning of the next major bear market.
Keywords: 330; Donald Trump; Iron Heel; major bear market; stock market; strategic sabotage